"It just fills you up": The culture of monthly community singing events in one American city. (October 2022) - Palkki, Joshua
This article conveys data collected in an ethnographic case study exploring monthly participatory community singing events in one city in the American Midwest. I analyze these data through the lens of a "traditional" choral conductor who, prior to undertaking this investigation, had little knowledge about participatory singing traditions; I also utilize scholarship about participatory versus presentational music activities as defined by Turino. Themes that arose during data analysis include: the context of folk music culture of Middletown, the inclusivity of community singing events, the role of the song-leader in facilitating these events, and "wounding stories" from participants who were discouraged by music educators. Perhaps in reflecting on the dichotomy between performative and participatory singing events, the choral community may begin to unlearn strictures that make some singers feel unwelcome.